Non-rod, non-cone photoreception in the vertebrates. - Foster, R; Hankins, M (2002)
When reflected from a surface, light can provide a representation of the spatial environment, whilst gross changes in environment light can signal the time of day. The differing sensory demands of using light to detect environmental space and time appear to have provided the selection pressures for the evolution of different photoreceptor systems in the vertebrates, and probably all animals. This point has been well recognised in the non-mammals, which possess multiple opsin/vitamin A-based photoreceptor populations in a variety of sites distributed both within and outside the CNS. By contrast, eye loss in mammals abolishes all responses to light, and as a result, all photoreception was attributed to the rods and cones of the retina. However, studies over the past decade have provided overwhelming evidence that the mammalian eye contains a novel photoreceptor system that does not depend upon the input from the rods and cones. Mice with eyes but lacking rod and cone photoreceptors can still detect light to regulate their circadian rhythms, suppress pineal melatonin, modify locomotor activity, and modulate pupil size. Furthermore, action spectra for some of these responses in rodents and humans have characterised at least one novel opsin/vitamin A-based photopigment, and molecular studies have identified a number of candidate genes for this photopigment. Parallel studies in fish showing that VA opsin photopigment is expressed within sub-sets of inner retina neurones, demonstrates that mammals are not alone in having inner retinal photoreceptors. It therefore seems likely that inner retinal photoreception will be a feature of all vertebrates. Current studies are directed towards an understanding of their mechanisms, determining the extent to which they contribute to physiology and behaviour in general, and establishing how they may interact with other photoreceptors, including the rods and cones. Progress on each of these topics is moving very rapidly. As a result, we hope this review will serve as an introduction to the cascade of papers that will emerge on these topics in the next few years. We also hope to convince the more casual reader that there is much more to vertebrate photoreceptors than the study of retinal rods and cones.